Condições do humor aquoso, quanto à contaminação, na facoemulsificação com implante de lente intraocular em cães - Lacerda, Luciana de Cenço Corrêa de [UNESP] (2014)
Phacoemulsification is the surgical treatment most commonly performed and accepted for cataracts. The use of artificial intraocular lens (IOL), indicated to achieve emetropy and as an aid on the prophylaxis of posterior capsule opacification, may, however, give rise to contamination arising from the nasal cavity and palpebral conjunctiva, in addition to the environment, the surgical staff, materials and instrumental. The goal of this research was to identify strains of bacteria present in the nasal and conjunctival secretions and aqueous humor of dogs undergoing phacoemulsification with implantation of intraocular lenses, as well as the characterization of genetic diversity among populations found using it sequencing of 16S rDNA of microorganisms, after selection of different groups by Rep-PCR with the primer BoxA1 associated BoxC1R. This study founded genders of bacteria like Enterobacter, Staphylococcus, Streptococcus and Pantoea and Staphylococcus aureus species. PCR-RFLP, using the enzyme MboI, identified Staphylococcus species such as S. pseudointermedius. Two copies of coagulase positive Staphylococcus aureus, founded by PCR, were confirmed by biochemical coagulase test. All of isolates was submitted by Rep-PCR with molecular markers Rep1R-I associated with Rep2, Eric2 and BoxC1R. It was found high genetic variability among them, especially regarding the gender Staphylococcus. Sequencing of 16S rDNA and Rep-PCR were effective in detecting genetic diversity. Eight isolates of gender Enterobacter in the conjunctival secretion and, at the same time, in aqueous humor, showed genetic distance of 0.000. Five percent of patients submitted to phacoemulsification with IOL implantation showed contamination in aqueous humor, by Enterobacter spp